The Role Of Parents In Developing The Independence Of Early Children During The Pandemic Period In Turekisa Village - Maria Karolina Ngao; Imanuel Lohmay; Angelikus Nama Koten (Early Childhood Education Development and Studies (ECEDS), 2022)
Purpose of this study was to describe the role of parents in developing independent learning for early childhood during the pandemic in Turekisa Village. This study uses a qualitative approach. There were 10 informants in this study, namely 5 parents who had children who were at an early age and lived in the village of Turekisa. The results of this study indicate that children's learning independence during the Covid-19 pandemic in Turekisa Village was quite good, all roles and attention were given by parents such as providing learning facilities, supervising children's learning activities at home, supervising the use of study time at home, monitoring children's learning difficulties, as well as parents help the difficulties faced by children in learning. Parents always provide encouragement and motivation in learning activities, because this encouragement can provide strength for each child to generate a willingness to learn, it's just that some have not been carried out optimally, because children have low learning independence due to the Covid-19 pandemic which makes learning activities are limited and more are done at home.